Relationship between customer personality, service features and customer loyalty in the banking sector: A survey of banks in Homabay County, Kenya - Onditi, Arvinlucy A. (Center for Promoting Ideas, USA, 2013)
Marketing management research has advocated for the establishment of the relationship between service features and customer loyalty in order to improve customer retention and organization performance. Despite consumer behavior theory emphasizing the importance of customer personality in consumer decision making process, establishing determinants of customer loyalty has been problematic. This study had a target population 845,000 and a sample size of 400 was selected from the population which included customers from Equity Bank, Kenya Commercial Bank, Barclays Bank and Cooperative Bank, to establish the relationship between customer personality, service features and customer loyalty in the banking sector in Homa Bay County. The study was guided by a conceptual framework involving concepts of customer loyalty and customer personality which are anchored on the theory of consumer behavior. The study used cross-sectional survey design, banks were selected using stratified sampling and the customers were picked using simple random sampling. Respondents were met at the ATM as they carry out their transactions. Data was collected using questionnaire and the reliability of the instrument was tested using split-half method while validity was tested by use of experts who were the supervisors of the researcher. Descriptive statistics, simple regression analysis, and moderated regression analysis were used to analyze data. The findings show that the independent variables service features is a significant determinants of customer loyalty among customers who had not that is service features (Fo=5.123˃Fc=3.860) after moderation (Fo=3.545˃Fc= 3.020). Among customers who had changed their banks, service features had no significant effect even after moderation with customer personality. The study concluded that customer personality has a moderating effect on the relationship between service features and customer loyalty. The study recommends that bank product managers should continuously modify their product offerings to suit their customers’ personality. The study may help the bank policy makers to predict customer loyalty using the models of customer loyalty, it also contributes to the development of consumer behavior theory.
Keywords: Customer loyalty; Service features; Banks; Homa Bay County; Customer switching behavior; Consumer Behavior; consumer decision-making